Sensors and control systems in manufacturing - Soloman, Sabrie, ....- (New York : McGraw-Hill, 2010)
A Comprehensive Guide to Sensors and Control Systems in Manufacturing Thoroughly updated with cutting-edge technologies, this detailed resource offers proven methods for effectively evaluating, selecting, and implementing sensors and controls to ensure error-free manufacturing environments. Sensors and Control Systems in Manufacturing, Second Edition offers step-by-step guidance on applying sensors to measure product parameters, control manufacturing, develop precision manufacturing systems, and generate and control motion. Real-world examples are included throughout to demonstrate successful industrial applications.
Includes bibliographical references and index.
Keywords: Automatic data collection systems; Process control -- Automation; Detectors